Catalán, D. y Facciano, B. (2024). Cartas a Odorico. Epistolario del beato Mamerto Esquiú a su hermano. San Antonio de Padua, Buenos Aires: Ediciones Castañeda - Nicolás Mario Andrés Molina (Antigua Matanza)
Reseña. No corresponde.